2006
DOI: 10.1108/eb059242
|View full text |Cite
|
Sign up to set email alerts
|

Managing Business Crises: The CSR Perspective

Abstract: When the chord of crisis strikes, test thy patience, virtuousness, friends and womanhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 1 publication
0
4
0
1
Order By: Relevance
“…A message that all companies should adopt would be "social activities discharge public accountability and disclosing such activities could provide a competitive edge". Sharma and Narwal (2006) observed that crisis is the real test of the capabilities, of both the organizations as well as individuals. The actions of three MNCs to get out of the crisis are analyzed from the CSR perspective.…”
Section: Review Of Literaturementioning
confidence: 99%
“…A message that all companies should adopt would be "social activities discharge public accountability and disclosing such activities could provide a competitive edge". Sharma and Narwal (2006) observed that crisis is the real test of the capabilities, of both the organizations as well as individuals. The actions of three MNCs to get out of the crisis are analyzed from the CSR perspective.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Organisations' capabilities are tested in times of crisis (Sharma & Narwal, 2006). Due to the fact that financial crisis are times of uncertainty, organisations tend to avoid negative effects by remedial actions; the most common actions are laying-off employees, decreasing consumption and postponing investments (Karaibrahimoglu, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Otras evidencias que se presentan en el documento son los estadísticos (Tabla 4), por lo cual, para este caso, no se puede validar la hipótesis de una menor divulgación en tiempos de crisis como sucede en los artículos elaborados por Jacob (2012); Sharma y Narwal (2006); Placier (2011). No obstante, en términos descriptivos, el sector de alimentos y bebidas reveló menor información con relación a empleados y productos y servicio al cliente, esto es apenas lógico dado que las políticas de confinamiento afectaron principalmente a los sectores gastronómicos y de entretenimiento (International Labour Organization [ILO], 2020); luego está el sector de educación, con una reducción de quince puntos porcentuales (pp).…”
Section: Discussionunclassified